LITERASI DIGITAL DAN ETIKA BERMEDIA SOSIAL PERSPEKTIF ISLAM: HUBUNGANNYA DENGAN SIKAP KRITIS DAN TANGGUNG JAWAB SISWA DALAM PEMBELAJARAN PAI DARING - Mabruri; Baili; Yanti, Ely; Khamim, Siti; Noviriani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The digital transformation of online Islamic Religious Education (PAI) presents both accessibility opportunities and ethical-cognitive challenges for students. This study aims to examine the relationship between digital literacy and Islamic perspective-based social media ethics with students' critical attitudes and responsibility in the context of online PAI learning. The research employed a quantitative correlational-explanatory design with a cross-sectional survey approach. The sample consisted of 186 junior and senior high school students participating in online/hybrid PAI learning, selected through proportional stratified random sampling. Instruments included scales for digital literacy (α=0.89), Islamic perspective-based social media ethics (α=0.91), critical attitude (α=0.88), and digital responsibility (α=0.90). Data were analyzed using Pearson correlation, multiple linear regression, and classical assumption tests. Results indicate that (1) digital literacy positively and significantly correlates with critical attitude (r=0.52; p=0.000) and responsibility (r=0.49; p=0.000); (2) Islamic perspective-based social media ethics shows a stronger positive correlation with critical attitude (r=0.58; p=0.000) and responsibility (r=0.63; p=0.000); (3) simultaneously, both predictor variables explain 68.4% of the variance in students' critical attitude and responsibility (R²=0.684; F=98.72; p=0.000), with Islamic ethics demonstrating more dominant predictive power (β=0.45–0.51). Findings confirm that the internalization of Islamic values in digital space functions as a moral compass that strengthens students' critical dispositions and accountability, surpassing mere technical digital literacy competencies. The study recommends integrating an Islamic digital adab framework into online PAI modules, teacher training based on digital citizenship, and strengthening school-family collaboration in ethical mentoring.